Pectenocaris gen. nov., a new Brazilian Parastenocaridinae Chappuis, 1940, and Afrocaris gen. nov., a West African Fontinalicaridinae Schminke, 2010 (Copepoda, Harpacticoida, Parastenocarididae) - Paulo Henrique Costa Corgosinho; Carlos Eduardo Falavigna Da Rocha (European Journal of Taxonomy)
This study focuses on the description of a new Parastenocaridinae species belonging to a new genus from Brazil’s Jalapão microregion and the establishment of a new genus for two West African Fontinalicaridinae species. Afrocaris gen. nov. and Pectenocaris gen. nov. differ in the morphology of the furca, with a gap between the outer setae I–III and the dorsal seta VII in Afrocaris gen. nov., and no gap between these elements in Pectenocaris gen. nov. The female genital field of Pectenocaris gen. nov. is rectangular and much broader than high than in other Parastenocaridinae. In Afrocaris gen. nov. the female endopod of the third pereopod is short, ending in a small tip, without a distal fused spine as in Pectenocaris gen. nov. Pectenocaris evilsoni gen. et sp. nov. is the type species of a new Parastenocaridinae genus. The maxillula praecoxal arthrite of Pectenocaris evilsoni is armed with six elements, a unique character within the family. The fourth pereopod of the male is heavily ornamented along the inner margin of the first and second exopodite, and cylindrical spinules with rounded tip are present on the basis, near the insertion of the short filiform endopod. The main characters supporting the new genus Afrocaris gen. nov. are the highly ornate inner margin of the first and second exopodites of the male fourth pereopod and the short fourth pereopod of the male endopod. The phylogenetic positions of Pectenocaris evilsoni gen. et sp. nov. and Afrocaris gen. nov. within their own subfamilies are challenging to ascertain due to the highly transformed male fourth pereopod in Pectenocaris evilsoni gen. et sp. nov. and the two species of Afrocaris gen. nov. as well as the absence of an intermediate condition in species closely related to each of these genera or a clear synapomorphy for a more inclusive group within each subfamily, requiring further field and morpho/molecular systematic work.